IMPACT OF MATERNAL HEALTH EDUCATION ON COMPLEMENTARY FEEDING PRACTICES IN URBAN AND RURAL AREAS OF MAHARASHTRA - Khan Arshad Tanvir; Manoj Mathew P (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Complementary feeding that starts at the age of six months is an important period of growth and development in a child. Complementary feeding is properly conducted with knowledge and practice as it provides good nutrition, increases immunity and prevents the occurrence of malnutrition and infection among infants. Maternal knowledge on health is critical in the determination of feeding habits in this stage. The current study will examine the effect of maternal health education on complementary feeding practices in rural and urban Maharashtra. The study was administered among 200 mothers (100 urban and 100 rural mothers) with their children of ages between 6 months and 2 years. The structured questionnaires based on structured interviews were used to collect information in relation to the knowledge, the source of information, and the actual practice of feeding the mother. The difference between groups was examined with help of the statistical means such as descriptive analysis and chi-square tests. This paper identifies the critical lack of maternal health education in rural locations, which should be found to fill the gap in knowledge. The enhancement of health communication strategies and the efforts that are aimed at educating the population on the said issue will contribute to feeding the population in a healthier manner and this issue is crucial to the well-being of children living both in the country and the city.